Revitalization of Mathematics Learning in Phase C: Implementing Teacher Strategies to Strengthen Conceptual Understanding in Elementary Schools - Novi Audria; Bunga Ayu Wulandari; Destrinelli Destrinelli (Lembaran Ilmu Kependidikan, 2025)
Background - Mathematics learning at the elementary level, especially at Phase C, requires innovative teaching strategies to enhance students’ conceptual understanding and motivation. Purpose - This study aims to explore and describe the strategies used by elementary school teachers to improve conceptual understanding in Phase C mathematics learning, focusing on their experiences and perceptions in implementing adaptive and innovative instructional approaches. Method/approach - A qualitative phenomenological method was employed to capture teachers’ lived experiences at SD Negeri 001/IV Kota Jambi during the 2024/2025 academic year. Data were collected through interviews, classroom observations, and document analysis involving two teachers, six students, and the principal. Data triangulation and member checking ensured the validity and reliability of the findings. Findings - The results reveal that teachers employ interactive and dynamic teaching strategies, use diverse teaching aids, implement constructivist approaches, conduct continuous assessments with direct feedback, collaborate in professional learning communities, and engage in comprehensive lesson planning. These strategies collectively enhance students’ conceptual understanding, foster active participation, and accommodate individual learning differences. Conclusions - The study provides empirical insights into effective teaching strategies that support adaptive and responsive mathematics instruction at Phase C in elementary schools. The integrated model of teaching strategies identified can serve as a valuable reference for improving mathematics education quality and innovation. Novelty/Originality/Value - This study offers a detailed phenomenological perspective on how teachers practically implement and adapt innovative instructional strategies in a real classroom context, bridging the gap between theory and practice in elementary mathematics education.